Determinants of Intercountry Prison Incarceration Rates and Overcrowding in Latin America and the Caribbean - Limoncelli, Katherine E. (International criminal justice review, 2020)
Research on prison population rates and prison overcrowding has largely been limited to U.S. populations. While these studies offer valuable insight into the broader-level factors affecting rates of imprisonment, along with correlates associated with pervasive levels of crowding, less is known about the macro-level causes of elevated imprisonment rates and increasingly high levels of prison crowding across Latin America and the Caribbean. A modified version of negative binomial random-effects model with between- and within-country transformations of time-varying covariates was utilized to test the influence of political, social, and economic factors on the prison population rate between countries and within countries over multiple time points. An ordinary least squares regression model was adopted to analyze the extent to which countries’ levels of political stability, government effectiveness, intentional homicide rates, and unemployment are related to national levels of prison overcrowding percentages. Findings demonstrate that government effectiveness and political stability are significantly and positively associated with increased prison population rates both between countries and within countries over time, while government effectiveness is simultaneously negatively related to prison overcrowding across countries.